IMMUNOMARKERS IN ACUTE CORONARY SYNDROME UPON ADMISSION AND ITS TRANSITION TO MYOCARDIAL INFARCTION - Marzhanat G. Alieva (Юг России: экология, развитие, 2017)
Abstract. The aim is to study and develop some prognostic criteria for the clinical outcome of acute coronary syndrome into myocardial infarction based on immunomarkers. Materials and methods. Are presented the results of examination of 85 patients admitted to the infarction department of the Republican Clinical Hospital of the Center for Specialized Emergency Medical Care in Makhachkala. Immunomarkers were determined by the methods of enzyme immunoassay and indirect immunofluorescence. Results. Of the studied markers of cardiospecific changes in the immunity system, the indices of the autoimmune response to antigenic substances of necrotic myocardium are most pronounced. An almost 3-fold increase in thrombus aspiration to cardiolipin was determined (p <0.01), and in 75% of cases, thrombus aspiration was determined for myocardial cells, mainly of the fibrillar type. The prognosis of clinical outcome of ACS in Q wave myocardial infarction at the hospital stage is associated with concentration intervals (separation points) of the following: immunomarkers: Neopterin from 20 to 28 nmol/L, TA to CL from 15 to 20 U/ml and 75% of cases there are TAs to myocardial cells. Patients who have these indicators at admission to the hospital  (reference point) are a high-risk group for the clinical outcome of ACS in Q wave -MI (endpoint). After calculating the general operating characteristics of the tests, we obtained concentration intervals for a block of cardiospecific immunomarkers: Se = 67%, Sp = 83%, PVP = 57%, PVN = 89%, DE = 80%, RR = 6.8. The presented indices of immunomarkers fall into the prognostic block of the scheme. Conclusion. The identification of a high-risk group of patients with ACS allows for early hospitalization to conduct treatment measures in accordance with standards of management of patients with occlusive lesions of coronary vessels causing large-focal myocardial infarction.